DSI: A Fully Distributed Spatial Index for Wireless Data Broadcast - LEE, Wang-Chien (Institutional Knowledge at Singapore Management University, 2005)
Recent announcement of the MSN Direct Service has demonstrated the feasibility and industrial interest in utilizing wireless broadcast for pervasive information services. To support location-based services in wireless data broadcast systems, a distributed spatial index (called DSI) is proposed in this paper. DSI is highly efficient because it has a linear yet fully distributed structure that facilitates multiple search paths to be naturally mixed together by sharing links. Moreover, DSI is very resilient in error-prone wireless communication environments. Search algorithms for two classical location-based queries, window queries and kNN queries, based on DSI are presented. Performance evaluation of DSI shows that DSI significantly outperforms R-tree and Hilbert Curve Index, two state-of-the-art spatial indexing techniques for wireless data broadcast